موقف محكمة العدل الدولية من شكوى غامبيا ضد ميانمار - شاكري، سمية (جامعة أدرار - مخبر القانون والمجتمع, 2020)
رفعت غامبيا شكوى أمام محكمة العدل الدولية ضد جمهورية میانمار بتاريخ 11 نوفمبر 2019، تتهم فيها دولة ميانمار بانتهاك اتفاقية منع جريمة الإبادة الجماعية والمعاقبة عليها، عقدت محكمة العدل الدولية جلستها للنظر في الشكوى يوم الثلاثاء 10 ديسمبر 2019. يعالج المقال مجموع الإجراءات المتخذة في إطار محكمة العدل الدولية منذ رفع الشكوى إلى صدور قرارها بتاريخ 23 جانفي 2020.
The Gambia filed a complaint with the International Court of Justice against the Republic of Myanmar on November 11, 2019, in which it complained of violations of the Genocide Convention, by the State of Myanmar against the Rohingya minority, the International Court of Justice held its hearing to consider the complaint on Tuesday 10 December 2019. The article deals with the totality of procedures taken within the International Court of Justice from the time the complaint was submitted to the issuance of its decision on January 23, 2020
Keywords: محكمة العدل الدولية -- غامبيا -- ميانمار -- الروهينغا -- الإبادة الجماعية